Revitalisasi Cerita Rakyat Kota Bengkulu Danau Dendam Tak Sudah Melalui Media Komik - Sari, Diana Yustita; Tarenza, Fariz Ardhi; Rianti, Mutiara Putri Nurdah; Atmaja, Loliek Kania (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This community service project aims to document existing folktales, with the legend of "Danau Dendam Tak Sudah" originating from Bengkulu, specifically in Dusun Besar Village, Singaran Pati District, Bengkulu City, Bengkulu Province. The current state of Bengkulu's local culture and folktales is disheartening, as Bengkulu folktales have minimal exposure to the public. The books containing Bengkulu folktales found in reading rooms are scarce, short-lived, and lack appeal. Therefore, to cultivate reading interest and simultaneously introduce and preserve the local wisdom of the "Danau Dendam Tak Sudah" story towards digital literacy, this community service program is presented in the form of comics. The methodology employed in implementing this service utilizes a field method. This approach is utilized to draw cultural conclusions from three sources: what people say, how people act, and the various artifacts people use. Comic media presents a more engaging narrative with illustrations and representations that make it easier for readers to comprehend a story.